Clinical significance of invasion distance relative to prognosis in pathological T3 colorectal cancer - Nomura, Masatoshi (Oncol Lett, 2019)
The T3 subdivision has been reported to predict prognosis in rectal cancer. However, few studies describe a correlation between T3 subdivision and prognosis in colon cancer. The current study aimed validate the correlation between the invasion distance (ID) beyond the muscularis propria and prognosis in colorectal cancer. The present retrospective study included 148 consecutive patients with pathologically confirmed T3 colorectal cancer, who underwent resection between January 2008 and October 2012. T3 stage was subdivided based on ID: T3a, ID<1 mm; T3b, ID=1–5 mm; and T3c, ID>5 mm. Statistical analyses were performed to evaluate correlations between T3 subdivision groups (T3a + T3b versus T3c) and clinicopathological factors. Compared with the T3a + T3b group, the T3c group exhibited worse 3-year RFS (P=0.003) and 5-year CSS (P=0.006). Multivariate analysis demonstrated that 3-year RFS was significantly correlated with sex (P=0.03) and ID (P=0.02), and 5-year CSS was significantly correlated with lymphoid dissection number (P=0.02) and ID (P=0.03). A ROC curve was constructed using ID values and recurrence data, and the area under the curve was 0.63. These data revealed that ID beyond the muscularis propria was significantly associated with prognosis in T3 colorectal cancer.